Belief Bias Effect in Older Adults: Roles of Working Memory and Need for Cognition - Ding, Daoqun; Chen, Yang; Lai, Ji; Chen, Xiyou; Han, Meng; Zhang, Xiangyi (Frontiers in Psychology, 2020)
Belief bias is the tendency to rely on prior beliefs rather than to obey fully the logical principles in syllogistic reasoning. Few studies have investigated the age effect on belief bias. Although several studies have recently begun exploring the age effect on belief bias, little is known about the psychological mechanisms underlying such effect. Accordingly, we investigated belief bias in older and young adults and explored the roles of working memory (WM) and need for cognition (NFC) between age and reasoning performance. We found that older adults showed a lower accuracy rate compared with young adults when conclusion believability and logical validity were incongruent. However, older adults showed a higher accuracy rate compared with young adults when conclusion believability and logical validity were congruent. Results indicated that in comparison with young adults, prior beliefs hampered logical reasoning more significantly for older adults under incongruent conditions and boosted logical reasoning more significantly under congruent conditions. Moreover, the logic index in older adults was significantly lower than young adults, and the interaction index of believability and validity in older adults was significantly below zero. Furthermore, NFC mediated the age effect on reasoning performance under the two conditions. By contrast, WM mediated the age effect on reasoning performance only under incongruent conditions and did not act as a mediator under congruent conditions.